Microalgae Cultivation in Open Pond and Photobioreactor - Dasa, Y.K. (Nova Science Publishers, Inc., 2021)
Microalgae biomass has a wide application in producing value-added products for the food, feed, cosmetics, and pharmaceutical industries. This necessitates an effective microalgae cultivation system to achieve maximum biomass productivity, tapping into the full potential of microalgae. The development of a cost-effective cultivation system is also important for an economically sustainable microalgae biorefinery system. To date, the typical commercial microalgae cultivation is either carried out in an open system or a closed one. Yet, the risk of contamination in the open system and high operating cost of the closed system pose a significant constraint for assessing the sustainability of producing value-added products from microalgae. In view of this, the development of a highly efficient microalgae production system remains a critical area of ongoing research. Therefore, this chapter provides valuable insights into the different ways to grow microalgae and the recent developments in microalgae cultivation techniques. Â© 2021 by Nova Science Publishers, Inc.